The Influence of Picture Story Books with a Local Wisdom Approach on Students' Learning Motivation in Primary School Mathematics Learning - Lubis, Azmil Hasan (MANDAILING GLOBAL EDUKASIA, 2025)
This study investigates the impact of illustrated storybooks that integrate local wisdom on elementary students’ motivation to learn mathematics. Drawing on constructivist learning theory and the concept of culturally responsive education, the research hypothesizes that pedagogical materials rooted in students’ cultural contexts can enhance intrinsic motivation and engagement in mathematical problem‑solving. A quasi‑experimental design was employed in three public primary schools in Central Java during the 2024‑2025 academic year. A total of 120 fourth‑grade learners were assigned to either an intervention group (n = 60) that received nine weeks of mathematics instruction supplemented by locally‑themed picture‑story books, or a control group (n = 60) that followed the standard curriculum using conventional textbook materials. Motivation was measured pre‑ and post‑intervention using the Mathematics Motivation Scale (MMS), which assesses intrinsic interest, self‑efficacy, and perceived relevance. Data were analyzed with analysis of covariance (ANCOVA) to control for baseline differences. Results indicate that the intervention group exhibited a statistically significant increase in overall motivation scores (M = 4.32, SD = 0.45) compared with the control group (M = 3.78, SD = 0.52), F(1, 116) = 15.27, p < 0.001, with notable gains in intrinsic interest and perceived relevance dimensions. Qualitative observations further revealed heightened classroom participation and more frequent self‑initiated problem‑solving behaviors among students exposed to the culturally‑infused storybooks. The findings suggest that integrating illustrated narratives reflecting local cultural values can effectively stimulate motivation in mathematics learning at the primary level. Implications for curriculum design, teacher training, and policy‑making toward culturally responsive pedagogy are discussed, alongside recommendations for longitudinal studies to examine sustained effects.